ESTIMATION OF ALUMINIUM LEVELS IN BLOOD, LIVER AND STOMACH CONTENTS USING ICP-AES: A CROSS-SECTIONAL AUTOPSY BASED STUDY (Journal of Forensic Medicine & Toxicology, 2022)
Aluminium(Al) is a naturally occurring trace element that makes up about 8% of the surface of earth. It is used in cooking utensils, containers, appliances, and building materials. It is also used in paints and fireworks, to produce glass, rubber and ceramics, and in consumer products such as antacids, astringents, buffered aspirin, food additives, and antiperspirants. Normal levels of Al in blood are
Keywords: Aluminium toxicity; ICP-AES; blood aluminium levels